2011
DOI: 10.1158/1535-7163.mct-11-0422
|View full text |Cite
|
Sign up to set email alerts
|

Antitumoral Effects of Calcitriol in Basal Cell Carcinomas Involve Inhibition of Hedgehog Signaling and Induction of Vitamin D Receptor Signaling and Differentiation

Abstract: Activation of the Hedgehog (Hh)-signaling pathway due to deficiency in the Hh receptor Patched1 (Ptch) is the pivotal defect leading to formation of basal cell carcinoma (BCC). Recent reports provided evidence of Ptch-dependent secretion of vitamin D 3 -related compound, which functions as an endogenous inhibitor of Hh signaling by repressing the activity of the signal transduction partner of Ptch, Smoothened (Smo). This suggests that Ptch-deficient tumor cells are devoid of this substance, which in turn resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 39 publications
(46 reference statements)
4
59
1
Order By: Relevance
“…39,116,118,134,135 These processes are regulated by cell-specific mechanisms and involve inhibition of hedgehog, β -catenin, NF κ B, and PI3K signaling pathways (refs 134,136,137 reviewed in refs 127,138). Apoptosis is also regulated by vitamin D. 1,25(OH) 2 D3-induced programmed cell death is mainly due to downregulation of the anti-apoptotic proteins Bcl-2 and Bcl-X L , upregulation of pro-apoptotic BAX, GOS2, DAP-3, FADD, and caspases (reviewed in refs 69,127,139).…”
Section: Vitamin D In a ‘Nutshell’mentioning
confidence: 99%
“…39,116,118,134,135 These processes are regulated by cell-specific mechanisms and involve inhibition of hedgehog, β -catenin, NF κ B, and PI3K signaling pathways (refs 134,136,137 reviewed in refs 127,138). Apoptosis is also regulated by vitamin D. 1,25(OH) 2 D3-induced programmed cell death is mainly due to downregulation of the anti-apoptotic proteins Bcl-2 and Bcl-X L , upregulation of pro-apoptotic BAX, GOS2, DAP-3, FADD, and caspases (reviewed in refs 69,127,139).…”
Section: Vitamin D In a ‘Nutshell’mentioning
confidence: 99%
“…Importantly, we recently demonstrated that calcitriol inhibits growth of basal cell carcinoma (BCC), which is an Hh/Ptch-driven tumor [18]. In BCC, the antitumoral property of calcitriol is accompanied by activation of the Vdr signaling pathway, by induction of differentiation and by simultaneous inhibition of Hh signaling activity [18].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of the Hedgehog molecules was inhibited by 1α,25(OH) 2 D 3 in mouse skin cells in a VDR-dependent manner [60]. In basal cell carcinoma, vitamin D 3 or 1α,25(OH) 2 D 3 inhibited Hedgehog signaling by repressing GLI1 mRNA and exerted anti-proliferative effects in vitro and in vivo [61,62]. Vitamin D 3 (cholecalciferol) also inhibited Hedgehog signaling by repressing GLI2 expression and tumor growth of renal carcinoma xenografts [63].…”
Section: Regulation Of Stem Cell Signaling By Vitamin D In Solid Tumentioning
confidence: 99%